2018
DOI: 10.1016/j.ijwd.2018.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Male versus female skin: What dermatologists and cosmeticians should know

Abstract: IntroductionThe skin is important for the perception of health and beauty. Knowledge of the physiological, chemical, and biophysical differences between the skin of male and female patients helps dermatologists develop a proper approach not only for the management of skin diseases but also to properly take care of cosmetic issues. The influence of genetic and environmental factors on skin characteristics is also critical to consider.MethodsA literature search of PubMed and Google was conducted to compare the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(121 citation statements)
references
References 57 publications
5
101
0
1
Order By: Relevance
“…Although several studies have been published on anatomical site‐ and gender‐related variation in human facial skin, the results are controversial . The aim of this study was to do a comprehensive assessment of the regional differences in facial skin biophysical properties in a Chinese population aged 22 in average, with special focus on changes over genders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although several studies have been published on anatomical site‐ and gender‐related variation in human facial skin, the results are controversial . The aim of this study was to do a comprehensive assessment of the regional differences in facial skin biophysical properties in a Chinese population aged 22 in average, with special focus on changes over genders.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the gender‐related variation in facial skin biophysical parameters, previous studies have shown that hydration, TEWL, sebum, skin thickness, pH, color, elasticity and friction were all different between male and female . The reported gender differences are usually occurred in group aged around 30 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subjects were stratified as described above, as gender‐related differences in the skin's matrix have been shown to have an effect on the viscoelastic properties considered in this study . However, to the authors’ knowledge, the literature regarding the effect of handedness on the viscoelastic properties of the skin is non‐existent.…”
Section: Methodsmentioning
confidence: 99%
“…Rahrovan et.al, 2018 reported SC rehydration capacity in sun-exposed aged female subjects was significantly lower than that of age-matched male subjects. The skin parameters of hydration, transepidermal water loss, sebum, microcirculation, pigmentation, and thickness are generally higher in men but skin pH is higher in women [75]. Trojahn et.al, 2015 reported that changes in skin elasticity, wrinkling, sagging, and yellowness seem to be caused by additional extrinsic ageing in women.…”
Section: E) Hormone and Metabolic Processesmentioning
confidence: 99%